Climate change knowledge among the community school students of Sindhuli district of central Nepal - K.C., Nishan; Thapa Chhetri, Vivek; Bhattarai, Suruchi; Subedi, Sanskar; Karki, Manish; Bhandari, Bishal; Sharma, Bikash; Acharya, Suman (Banko Janakari, 2023)
Knowledge of climate change is a key instrument to combat climate change and raise awareness of society, but only a few studies have been conducted to assess students’ knowledge level in Nepal. In this study, a semi-structured questionnaire survey was conducted on 140 students of grades 7, 8, 9, and 10 from four community schools to assess climate change knowledge. The results showed a statistically significant association between students’ responses to being aware (yes/no) of the term “climate change” across genders as well as across different grades. A majority of the surveyed students reported a rise in temperature (n=67.85 %) and increasing rainfall intensity (n=57.85 %) over the course of the years. More than half of the surveyed students (n=55 %) would like to receive climate change education through their own curriculum books. Similarly, 44.27 % of the surveyed students identified plantation activities as a key climate change adaptation measure that they could perform. The findings of our study has indicated that school education is the best medium for students to learn about climate change. Thus, environmental education programs should be widely promoted while climate change education needs to be integrated into school curricula to a greater extent.